Modified sulfide solid electrolyte

JP2026166149APending Publication Date: 2026-10-14IDEMITSU KOSAN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058922
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、耐酸化性に優れた改質硫化物固体電解質を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166149000003
    Figure 2026166149000003
  • Figure 2026166149000004
    Figure 2026166149000004
  • Figure 2026166149000005
    Figure 2026166149000005
Patent Text Reader

Abstract

A modified sulfide solid electrolyte having excellent oxidation resistance is provided. 【Solution Means】 A modified sulfide solid electrolyte comprising a sulfide solid electrolyte having a BET specific surface area of 15 m 2 / g or more and 35 m 2 / g or less, and a compound containing carbon atoms and oxygen atoms, wherein the ratio (B P2p ) of the area ratio (B S2p ) of C-O derived from the compound in the O1s spectrum, relative to the sum of the composition ratio (A C-O ) of the P2p spectrum and the composition ratio (A C-O ) of the S2p spectrum at the outermost surface measured by X-ray photoelectron spectroscopy (XPS), (B P2p / (A S2p +A)) is 0.010 or more and 0.075 less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to modified sulfide solid electrolytes. [Background technology]

[0002] In recent years, with the rapid proliferation of information-related devices and communication equipment such as personal computers, video cameras, and mobile phones, the development of batteries used as power sources has become increasingly important. Traditionally, batteries used in such applications have employed electrolytes containing flammable organic solvents. However, because the electrolyte is both liquid and flammable, there are safety concerns regarding leakage, ignition, and other issues when used in batteries. In particular, in automotive applications, there is a demand for higher capacity and higher output, and concerns about the safety of conventional batteries using electrolytes are growing. Therefore, by making batteries entirely solid, it is possible to eliminate the use of flammable organic solvents within the battery, simplify safety devices, and improve manufacturing costs and productivity. As a result, development of all-solid-state batteries, in which the electrolyte is replaced with a solid electrolyte layer, is underway.

[0003] Sulfide solid electrolytes have been conventionally known as solid electrolytes used in solid electrolyte layers. High oxidation-reduction resistance (also simply referred to as "oxidation resistance") is desired for sulfide solid electrolytes, and there is also a growing demand for improved battery performance when used in lithium-ion batteries. As methods to improve these properties, techniques such as coating the surface of the solid electrolyte and using it as a composition containing the solid electrolyte and an organic compound are being investigated.

[0004] For example, Patent Document 1 describes a modified sulfide solid electrolyte that, even if it has a large specific surface area, exhibits excellent coating suitability when applied as a paste and can efficiently achieve excellent battery performance, with a specific surface area of ​​10 m². 2 A modified sulfide solid electrolyte has been proposed that contains a sulfide solid electrolyte of 1 / g or more and an epoxy compound, and has a predetermined peak in the infrared absorption spectrum obtained by FT-IR analysis (ATR method). [Prior art documents]

Patent Documents

[0005]

Patent Document 1

Summary of the Invention

Problem to be Solved by the Invention

[0006] The present invention has been made in view of such actual circumstances, and an object thereof is to provide a modified sulfide solid electrolyte having excellent oxidation resistance.

Means for Solving the Problem

[0007] The modified sulfide solid electrolyte according to the present invention comprises: a sulfide solid electrolyte having a BET specific surface area of 15 m 2 / g or more and 35 m 2 / g or less, and a compound containing carbon atoms and oxygen atoms, wherein the ratio of the area ratio (B P2p ) of C-O derived from the aforementioned compound in the O1s spectrum, out of the sum of the composition ratio (A S2p ) of the P2p spectrum and the composition ratio (A C-O ) of the S2p spectrum at the outermost surface measured by X-ray photoelectron spectroscopy (XPS), that is (B C-O / (A P2p +A S2p )) is 0.010 or more and 0.075 or less.

Effects of the Invention

[0008] According to the present invention, a modified sulfide solid electrolyte having excellent oxidation resistance can be provided.

Brief Description of the Drawings

[0009] [Figure 1] These are X-ray photoelectron spectroscopy (XPS) measurement spectra of the modified sulfide solid electrolytes of Examples 1, 4 and 6, and the sulfide solid electrolyte of Comparative Example 1. [Figure 2]These are the CV curves at the 5th cycle of the CV measurement for the modified sulfide solid electrolytes of Examples 1-6 and the sulfide solid electrolyte of Comparative Example 1. [Figure 3] This is the spectrum obtained by solid-state 1H-6Li CP / MAS NMR measurement of the modified sulfide solid electrolyte of Example 1. [Figure 4] This is the spectrum obtained by solid-state 1H-6Li CP / MAS NMR measurement of the modified sulfide solid electrolyte of Example 4. [Figure 5] This is the spectrum obtained by solid-state 1H-6Li CP / MAS NMR measurement of the modified sulfide solid electrolyte of Example 6. [Figure 6] This is the spectrum obtained by solid-state 1H-6Li CP / MAS NMR measurement of the sulfide solid electrolyte of Comparative Example 1. [Modes for carrying out the invention]

[0010] The embodiments of the present invention (hereinafter sometimes referred to as "these embodiments") will be described below. In this specification, the upper and lower limit values ​​related to the numerical ranges indicated by "greater than or equal to," "less than or equal to," and "~" can be any combination of values, and the values ​​in the examples can also be used as the upper and lower limit values.

[0011] (Knowledge gained by the inventors in arriving at the present invention) The inventors of this invention diligently studied and, as a result of their efforts to solve the above problems, discovered the following and completed the present invention. As described in Patent Document 1, techniques for coating or incorporating a compound onto the surface of a sulfide solid electrolyte have existed for some time. Patent Document 1 discloses a modified sulfide solid electrolyte that, even if it has a large specific surface area, exhibits excellent coating suitability when applied as a paste and can efficiently exhibit excellent battery performance. 2 / g and 40m 2Detailed studies have been conducted on sulfide solid electrolytes having a specific surface area of ​​1 / g, and modified sulfide solid electrolytes with excellent coating properties and superior battery performance have been obtained by modifying these specific surface areas. Incidentally, in the region with a relatively large specific surface area, namely 15-35m², 2 There is a growing demand for sulfide solid electrolytes with a specific surface area of ​​1 / g. The inventors of this invention conducted detailed studies on sulfide solid electrolytes with relatively large specific surface areas, including surface analysis using X-ray photoelectron spectroscopy (XPS), and discovered that they exhibit unique phenomena.

[0012] More specifically, according to X-ray photoelectron spectroscopy (XPS) measurement results, it was found that in the relationship between the O1s spectrum originating from a compound containing carbon and oxygen atoms (hereinafter sometimes simply referred to as "coating material") and the P2p and S2p spectra originating from a sulfide solid electrolyte, if the ratio of the area of ​​CO in the O1s spectrum originating from the compound to the composition ratio of the P2p and S2p spectra of the outermost surface is within a predetermined range, the reduction in ionic conductivity is suppressed, maintaining high ionic conductivity while achieving extremely high oxidation resistance. This phenomenon is studied in detail in Patent Document 1 for 10m 2 / g and 40m 2 This phenomenon has not been observed in sulfide solid electrolytes with a specific surface area of ​​1 / g. X-ray photoelectron spectroscopy (XPS) measurements show that similar results are obtained across the entire surface of the sulfide solid electrolyte. Therefore, it is thought that when a coating material is brought into contact with a sulfide solid electrolyte with a relatively large specific surface area, the coating material does not adhere locally but rather spreads and adheres to the surface. The reason why the coating material adheres to the surface of sulfide solid electrolytes with a relatively large specific surface area by spreading is not clear, but it is presumed that the uneven surface shape of sulfide solid electrolytes with a relatively large specific surface area makes it easy for the coating material to adhere in a spreading manner due to factors such as surface tension and wettability. As a result, it is thought that excellent oxidation resistance is obtained.

[0013] Based on the above considerations, the inventors of the present invention have found that 15-35m 2 We have discovered that by combining a sulfide solid electrolyte with a relatively large specific surface area of ​​1 / g with a compound containing carbon and oxygen atoms, and by setting the ratio of the area of ​​CO derived from the compound in the O1s spectrum to the sum of the composition ratios of the S2p spectrum and P2p spectrum at the outermost surface to be within a specific range, it is possible to create a modified sulfide solid electrolyte with excellent oxidation resistance while minimizing the decrease in the ionic conductivity of the sulfide solid electrolyte. Furthermore, since the compound containing carbon and oxygen atoms mainly exists as a coating on the surface of the sulfide solid electrolyte, it is generally considered that the ionic conductivity tends to decrease. However, the effect of minimizing the decrease in ionic conductivity is a significant advantage for sulfide solid electrolytes.

[0014] (Regarding various forms of this embodiment) The modified sulfide solid electrolyte according to the first embodiment of this present invention is BET specific surface area is 15m 2 / g or more 35m 2 A sulfide solid electrolyte containing a concentration of 0.5 / g or less, and a compound containing carbon and oxygen atoms, is used, and the composition ratio of the P2p spectrum of the outermost surface, measured by X-ray photoelectron spectroscopy (XPS), is (A P2p ) and composition ratio of the S2p spectrum (A S2p The area ratio of CO derived from the compound in the O1s spectrum to the total of (B C-O ) ratio (B C-O / ( A P2p +A S2p It is a modified sulfide solid electrolyte whose ratio is between 0.010 and 0.075.

[0015] In this specification, "sulfide solid electrolyte" means an electrolyte that contains sulfur atoms and maintains a solid state at 25°C under a nitrogen atmosphere. In this embodiment, the sulfide solid electrolyte preferably contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and has ionic conductivity due to the lithium atoms.

[0016] "Sulfide solid electrolytes" include both crystalline sulfide solid electrolytes, which have a crystalline structure, and amorphous sulfide solid electrolytes. In this specification, a crystalline sulfide solid electrolyte is a solid electrolyte in which a peak originating from the solid electrolyte is observed in the X-ray diffraction pattern in an X-ray diffraction measurement, regardless of whether or not a peak originating from the raw material of the solid electrolyte is observed. That is, a crystalline sulfide solid electrolyte includes a crystalline structure derived from the solid electrolyte, and may be partially derived from the solid electrolyte or entirely derived from the solid electrolyte. Furthermore, if a crystalline sulfide solid electrolyte has the above-described X-ray diffraction pattern, it may also contain amorphous sulfide solid electrolyte (also referred to as "glass component"). Therefore, crystalline sulfide solid electrolytes include so-called glass ceramics obtained by heating amorphous sulfide solid electrolyte (glass component) above its crystallization temperature.

[0017] Furthermore, in this specification, amorphous sulfide solid electrolytes (glass components) refer to those that exhibit a halo pattern in X-ray diffraction measurements where peaks other than those originating from the raw materials are substantially absent, regardless of whether or not peaks originating from the raw materials of the solid electrolyte are present. The above distinction between crystalline and amorphous materials applies to both sulfide solid electrolytes and modified sulfide solid electrolytes in this embodiment.

[0018] As previously mentioned, depending on the BET specific surface area of ​​the sulfide solid electrolyte, it may not be possible to adequately cover the surface, and thus the battery performance may not be improved. The inventors of this invention have found that 15-35m 2We have found that by combining a sulfide solid electrolyte having a relatively large specific surface area of ​​1 / g with a compound containing carbon and oxygen atoms, and by setting the ratio of the area of ​​CO derived from the compound in the O1s spectrum to the sum of the composition ratios of specific P2p and S2p spectra to be within a specific range, the oxidation resistance of the sulfide solid electrolyte is improved while minimizing the decrease in ionic conductivity. In other words, the modified sulfide solid electrolyte of this embodiment has improved oxidation resistance while minimizing the decrease in ionic conductivity, thus "modifying" the properties of ionic conductivity and oxidation resistance that sulfide solid electrolytes possess, and should be called a "modified sulfide solid electrolyte."

[0019] The modified sulfide solid electrolyte according to the second embodiment of this invention is, in the first embodiment described above, The content of the compound containing carbon atoms and oxygen atoms is 0.03 parts by mass or more and 25 parts by mass or less per 100 parts by mass of the sulfide solid electrolyte. That is the case.

[0020] When the content of compounds containing carbon and oxygen atoms is within the above range, it becomes easier to more efficiently and uniformly coat the surface of the sulfide solid electrolyte with the compounds, thereby minimizing the decrease in ionic conductivity and making it easier to obtain excellent oxidation resistance.

[0021] The modified sulfide solid electrolyte according to the third embodiment of this embodiment is, in the first or second embodiment described above, The compound containing the carbon atom and oxygen atom is a compound having an epoxy group. That is the case.

[0022] In this embodiment, if the modified sulfide solid electrolyte contains a compound having an epoxy group, the adhesion between the surface of the sulfide solid electrolyte and the compound is improved, the surface is more uniformly coated by the compound, the decrease in ionic conductivity is minimized, and excellent oxidation resistance is more easily obtained.

[0023] The modified sulfide solid electrolyte according to the fourth embodiment of this embodiment is, in any one of the first to third embodiments described above, solid 1 H- 6 The area of ​​the broad peak observed in Li CP / MAS NMR measurements at chemical shifts of 0.5–1.2 ppm (A B ) and the area of ​​the sharp peak at chemical shift -0.2~0.5 ppm (A S The area of ​​the peak at 0.5 to 1.2 ppm relative to the total area of ​​(A B The ratio of ) is between 10.0% and 65.0%. That is the case.

[0024] Regarding the modified sulfide solid electrolyte of this embodiment, 1 H- 6 When measured by Li CP / MAS NMR, it is preferable that the modified sulfide solid electrolyte of this embodiment has peaks at chemical shifts of 0.5 to 1.2 ppm and -0.2 to 0.5 ppm, and that the areas of these peaks have the above-mentioned relationship. By having these peaks with the above-mentioned relationship in terms of peak area, the decrease in ionic conductivity is suppressed as much as possible, and the modified sulfide solid electrolyte of this embodiment has superior oxidation resistance.

[0025] Among the peaks in the chemical shift range of -0.2 to 1.2 ppm, the broad peak in the chemical shift range of 0.5 to 1.2 ppm is considered to be a peak resulting from the presence of compounds containing carbon and oxygen atoms, as can be seen from the comparison between the examples and comparative examples described later. This is supported by the fact that the area of ​​the broad peak increases as the content of compounds containing carbon and oxygen atoms increases. In the above-mentioned terms "broad peak" and "sharp peak," "broad" and "sharp" refer to the peaks detected in the chemical shift range of -0.2 to 1.2 ppm, respectively, meaning that the peaks are relatively broad and sharp, respectively. Relatively broad peaks are detected at 0.5 to 1.2 ppm, and relatively sharp peaks are detected at -0.2 to 0.5 ppm. In this specification, "broad" means "broad" in relation to other peaks, but it may also be considered "broad" if the full width at half maximum is 50 Hz or more, i.e., if the full width at half maximum is less than 50 Hz, it may also be considered "sharp."

[0026] The phenomenon of broad peaks occurring can be explained as follows: As the compound containing carbon atoms and oxygen atoms, it is preferable to use an organic compound containing carbon atoms and oxygen atoms, as described later; that is, a compound containing hydrogen atoms in addition to carbon atoms and oxygen atoms is preferably used. In this case, the modified sulfide solid electrolyte of this embodiment is solid 1 H- 6 Li CP / MAS NMR measurements reveal that hydrogen atoms in compounds containing hydrogen atoms in addition to carbon and oxygen atoms ( 1 Lithium atoms located near H) 6 A peak attributable to this lithium atom (Li) is detected. 6 The peak attributed to Li) is a peak that appears because compounds containing carbon and oxygen atoms are used, and therefore, as mentioned above, it is considered to be a peak that arises from the presence of compounds containing carbon and oxygen atoms while coating the material.

[0027] It is generally known that the peak shape broadens as the mobility of the target atom decreases. Lithium atom ( 6 The peak caused by Li is detected as a broad peak with a full width at half maximum of 50 Hz or more because of the interaction with the oxygen atom of a compound containing carbon and oxygen atoms, which affects the lithium atoms contained in the sulfide solid electrolyte. 6 It is thought that the mobility of Li decreases, resulting in a broadening of the peak shape. Furthermore, it is believed that the interaction between the oxygen atom and the lithium atom allows for the suppression of the decrease in ionic conductivity while efficiently obtaining the improved oxidation resistance that is a benefit of using compounds containing carbon and oxygen atoms. Furthermore, the effect of improving oxidation resistance can be considered as follows: The improvement in oxidation resistance is achieved by suppressing the oxidation of the sulfide solid electrolyte by presenting an electrochemically stable compound on the surface of the sulfide solid electrolyte, which is the starting point of oxidation. In addition, the broad peak at chemical shift 0.5 to 1.2 ppm indicates a decrease in the mobility of lithium atoms, but it means that lithium ion conductivity is present, so the decrease in ionic conductivity can be suppressed as much as possible. In this way, by coating the surface with a compound that is electrochemically stable and lithium conductive, a sulfide solid electrolyte with improved oxidation resistance can be obtained while suppressing the decrease in the sulfide-based solid electroionic conductivity as much as possible.

[0028] The modified sulfide solid electrolyte according to the fifth embodiment of this present invention is, in any one of the first to fourth embodiments described above, The decrease rate of the oxidation current measured by cyclic voltammetry (CV measurement), calculated using the following formula, is 3.0% or higher. That is the case. The percentage decrease in oxidation current (%) = (oxidation current 2 - oxidation current 1) / oxidation current 2 × 100 Oxidation current 1: Oxidation current (mA) of the modified sulfide solid electrolyte. Oxidation current 2: Oxidation current (mA) of the sulfide solid electrolyte before modification.

[0029] The smaller the oxidation current, the better the oxidation resistance. Therefore, the larger the rate of decrease in the oxidation current, the better the oxidation resistance and the superior the oxidation resistance. The modified sulfide solid electrolyte of this embodiment preferably has a rate of decrease in oxidation current of 3.0% or more, thus exhibiting superior oxidation resistance.

[0030] The modified sulfide solid electrolyte according to the sixth embodiment of this embodiment is, in any one of the first to fifth embodiments described above, The sulfide solid electrolyte comprises lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms. That is the case.

[0031] The modified sulfide solid electrolyte of this embodiment has higher ionic conductivity because the sulfide solid electrolyte contains the above-mentioned constituent atoms, and in particular, halogen atoms, which improves its ionic conductivity.

[0032] The modified sulfide solid electrolyte according to the seventh embodiment of this present invention is, in any one of the first to sixth embodiments described above, The sulfide solid electrolyte includes at least one of the following crystal structures: a thiolysicon region type II crystal structure and an argyrodite type crystal structure. That is the case.

[0033] Sulfide solid electrolytes having at least one of the thiolysicon region II crystal structure and argyrodite crystal structure have extremely high ionic conductivity. The modified sulfide solid electrolyte of this embodiment has even higher ionic conductivity by including at least one of the thiolysicon region II crystal structure and argyrodite crystal structure.

[0034] The modified sulfide solid electrolyte of this embodiment will be described in more detail below, in accordance with the above-described aspects.

[0035] [Modified sulfide solid electrolyte] The modified sulfide solid electrolyte of this embodiment is BET specific surface area is 15m 2 / g or more 35m 2 A sulfide solid electrolyte containing a concentration of 0.5 / g or less, and a compound containing carbon and oxygen atoms, is used, and the composition ratio of the P2p spectrum of the outermost surface, measured by X-ray photoelectron spectroscopy (XPS), is (A P2p ) and composition ratio of the S2p spectrum (A S2p The area ratio of CO derived from the compound in the O1s spectrum to the total of (B C-O ) ratio (B C-O / ( A P2p +A S2p )) is between 0.010 and 0.075. It is a modified sulfide solid electrolyte.

[0036] The modified sulfide solid electrolyte of this embodiment contains a sulfide solid electrolyte and a compound containing carbon and oxygen atoms (hereinafter also referred to as "coating material"). Therefore, by X-ray photoelectron spectroscopy (XPS), P2p spectra and S2p spectra originating from the sulfide solid electrolyte and O1s spectra originating from the coating material are observed. The sum of the composition ratios of the P2p spectra and S2p spectra originating from the sulfide solid electrolyte is (A P2p +A S2p ) the area ratio of CO due to the coating material in the O1s spectrum (B C-O ) ratio (B C-O / ( A P2p +A S2p A ratio of 0.010 to 0.075 allows for excellent oxidation resistance while minimizing the decrease in ionic conductivity. The fact that this ratio is between 0.010 and 0.075 suggests that, as mentioned above, the uneven surface shape of the sulfide solid electrolyte, which has a relatively large specific surface area, allows the coating material to adhere in a spreading manner due to factors such as surface tension and wettability. As a result, excellent oxidation resistance is obtained while minimizing the decrease in ionic conductivity.

[0037] In this specification, the P2p spectrum, S2p spectrum, and O1s spectrum are spectra observed when narrow-scan measurements are performed on the elements phosphorus, sulfur, and oxygen using an XPS analyzer. The peak of the P2p spectrum is observed at 132 eV, the peak of the S2p spectrum is observed at 162 eV, and the peak of the O1s spectrum is observed at 532 eV. Note that the positions of these peaks may vary within a range of ±5 eV. The compositional ratios of the spectra of these elements are, respectively, A P2p , A S2p , the area ratio of CO due to the coating material in the O1s spectrum is B C-O Let the ratio be (B C-O / ( A P2p +A S2p The following was determined. For a more detailed measurement method, you can follow the method described in the examples below.

[0038] (Sulfide solid electrolyte) The sulfide solid electrolyte used in this embodiment has a BET specific surface area of ​​15 m². 2 / g or more 35m 2 The BET specific surface area of ​​the sulfide solid electrolyte is less than or equal to / g. When the BET specific surface area of ​​the sulfide solid electrolyte is within the above range, adhesion with compounds (coating materials) containing carbon and oxygen atoms is improved, the surface is more easily coated with the compound, the decrease in ionic conductivity is suppressed as much as possible, and excellent oxidation resistance is easily obtained. From this viewpoint, the BET specific surface area of ​​the sulfide solid electrolyte used in this embodiment is preferably 18m². 2 / g or more 32m 2 / g or less, more preferably 20m 2 / g or more 30m 2 It is less than / g. In this specification, the BET specific surface area is the specific surface area measured using nitrogen gas as the adsorbate, in accordance with JIS Z 8830:2013 (Method for measuring the specific surface area of ​​powders (solids) by gas adsorption).

[0039] The sulfide solid electrolyte used in this embodiment preferably contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms. The inclusion of these constituent atoms in the sulfide solid electrolyte further improves its ionic conductivity.

[0040] (Manufacturing of sulfide solid electrolytes) The sulfide solid electrolyte that can be used in this embodiment contains sulfur atoms and has a BET specific surface area of ​​15 m². 2 / g or more 35m 2 Any solid electrolyte with a concentration of less than / g can be used without any particular restrictions; commercially available products can be used as is, or they can be manufactured and used. The method for producing and using a sulfide solid electrolyte that can be used in this embodiment will be described. The sulfide solid electrolyte that can be used in this embodiment is obtained by a production method that includes mixing two or more raw materials selected from compounds containing at least one atom, preferably a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom.

[0041] (raw materials) Preferably, two or more substances selected from compounds containing at least one of the following atoms can be used as raw materials: lithium, sulfur, phosphorus, and halogen. It is preferable that the two or more substances, as a whole, contain lithium, sulfur, phosphorus, and halogen atoms. In other words, it is preferable to use substances such that a sulfide solid electrolyte containing lithium, sulfur, phosphorus, and halogen atoms can be obtained. As for materials that can be used as raw materials, those containing at least one atom from lithium, sulfur, phosphorus, and halogen atoms are typically preferred. More specifically, raw materials containing at least two atoms selected from the above atoms, such as lithium sulfide; phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); and raw materials consisting of one atom selected from the above atoms, such as phosphorus molecules and sulfur molecules. Among these, lithium sulfide and phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5) are preferred, and among phosphorus sulfides, phosphorus pentasulfide (P2S5) is preferred.

[0042] Furthermore, substances containing halogen atoms can also be used as raw materials. For example, lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; halogen molecules such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2) are typically preferred.

[0043] In the method for producing a sulfide solid electrolyte of this embodiment, the above raw materials can be used in a blending ratio that matches the composition of the sulfide solid electrolyte to be obtained. Examples of the blending ratio of lithium sulfide to other raw materials include those described in International Publication No. 2020 / 105737 (see paragraphs

[0024] to

[0028] ), etc. Furthermore, the raw materials can also be appropriately selected from substances exemplified in International Publication No. 2020 / 105737 (see paragraphs

[0020] to

[0022] ), Japanese Patent Application Publication No. 2024-116072 (see paragraphs

[0101] to

[0109] ), etc.

[0044] (mixture) The mixing of two or more raw materials selected from substances containing at least one atom of lithium, sulfur, phosphorus, and halogen is not particularly limited in terms of the method, as long as the above raw materials can be mixed. For example, the mixing of raw materials can be carried out using a pulverizer, mixer, agitator, etc. Using a pulverizer will result in the pulverization of the raw materials, but mixing will also occur simultaneously. Mixing of raw materials can also occur when using a mixer and agitator. Therefore, it can be said that the sulfide solid electrolyte that can be used in this embodiment can preferably be produced by stirring, mixing, pulverizing, or a combination of any of the following processes using two or more raw materials selected from substances containing at least one atom of lithium, sulfur, phosphorus, and halogen.

[0045] Regarding the equipment used for mixing raw materials, such as pulverizers, mixers, and agitators, there are no particular restrictions on the use of commonly available equipment.

[0046] In the above mixing process, a solvent can be added to the above raw materials and mixed. As the solvent, a wide range of solvents conventionally used in the production of solid electrolytes can be used, and hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents are preferred.

[0047] In addition to the hydrocarbon solvents mentioned above, other solvents that may be used include those containing atoms other than carbon atoms and hydrogen atoms, such as heteroatoms like nitrogen atoms, oxygen atoms, sulfur atoms, and halogen atoms. Such solvents have the property of readily forming complexes (which can also be called "electrolyte precursors" because sulfide solid electrolytes can be obtained by removing the complexing agent from the "complex") with raw materials containing lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms used as raw materials (hereinafter, such solvents will also be called "complexing agents"). By forming complexes, halogen atoms can be more easily retained within the structure of the sulfide solid electrolyte, which is useful in that it allows for higher ionic conductivity. Furthermore, when complexing agents are used, the reaction of the raw materials can proceed simply by using equipment such as mixers and stirrers, i.e., without using pulverizers, making them extremely useful in the production of sulfide solid electrolytes.

[0048] As the complexing agent and hydrocarbon solvent that can be used, for example, the complexing agents and hydrocarbon solvents exemplified in International Publication No. 2020 / 105737, etc., can be used. As a complexing agent, among solvents containing these heteroatoms, it is preferable to use a solvent containing a nitrogen atom, more preferably an amine solvent having an amino group, and even more preferably a diamine solvent having two amino groups.

[0049] (Drying) If mixing is performed using a solvent, the mixture may be dried after mixing (usually a slurry). If a complexing agent is used as the solvent, the sulfide solid electrolyte is obtained by removing the complexing agent from the complex containing the complexing agent; if a complexing agent and a solvent are used in combination, the complexing agent is removed from the complex containing the complexing agent and the solvent is removed; and if a solvent other than a complexing agent is used, the solvent is removed. The obtained sulfide solid electrolyte exhibits ionic conductivity due to lithium atoms.

[0050] The drying method can be any method that can remove the solvent, and can be performed using solid-liquid separation, drying by heating, reduced-pressure drying (vacuum drying), or a combination of these methods. When using a complexing agent as a solvent to remove the complexing agent from the complex (electrolyte precursor), drying by heating is preferred, and it is preferable to carry out the drying using a dryer such as a flow-through heater. Since the complexing agent can be removed from the complex (electrolyte precursor) quickly, the generation of impurities can be suppressed more efficiently, and a high-quality sulfide solid electrolyte can be obtained. Preferred flow-through heaters include airflow dryers, spray dryers, and fluidized bed dryers using a medium, with airflow dryers being the most preferred among them.

[0051] (heating) When producing a crystalline sulfide solid electrolyte, further heating may be included. If an amorphous sulfide solid electrolyte (glass component) is obtained by the above mixing, heating will yield a crystalline sulfide solid electrolyte. If a crystalline sulfide solid electrolyte is obtained, a crystalline sulfide solid electrolyte with improved crystallinity can be obtained. In either case, heating can make the obtained sulfide solid electrolyte a crystalline sulfide solid electrolyte and improve its ionic conductivity. In other words, the above heating can be considered an operation performed for crystallization.

[0052] When a complexing agent is used as a solvent during mixing, a complex containing the complexing agent is formed. However, by heating without drying as described above, the complexing agent can be removed from the complex, and a sulfide solid electrolyte can be obtained. Depending on the heating conditions, it can be amorphous or crystalline.

[0053] (Amorphous sulfide solid electrolyte) The amorphous sulfide solid electrolyte obtained by the above method contains lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms. Typical examples include sulfide solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr; and preferably sulfide solid electrolytes further containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI and Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ionic conductivity, sulfide solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr, are preferred, and sulfide solid electrolytes composed of lithium sulfide, phosphorus sulfide, and two types of lithium halide, such as Li2S-P2S5-LiI-LiBr, are more preferred. The types of atoms constituting amorphous sulfide solid electrolytes can be determined, for example, by an ICP emission spectrometer.

[0054] In amorphous sulfide solid electrolytes, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms is preferably 1.0~1.8:0.1~0.8:1.0~2.0:0.01~0.6, more preferably 1.1~1.7:0.2~0.6:1.2~1.8:0.05~0.5, and even more preferably 1.2~1.6:0.25~0.5:1.3~1.7:0.08~0.4. Furthermore, when bromine and iodine, or bromine and chlorine are used in combination as halogen atoms, the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, bromine, and iodine (or chlorine) is preferably 1.0~1.8:0.1~0.8:1.0~2.0:0.01~0.3:0.01~0.3, more preferably 1.1~1.7:0.2~0.6:1.2~1.8:0.02~0.25:0.02~0.25, even more preferably 1.2~1.6:0.25~0.5:1.3~1.7:0.03~0.2:0.03~0.2, and even more preferably 1.35~1.45:0.3~0.45:1.4~1.7:0.04~0.18:0.04~0.18.

[0055] There are no particular restrictions on the shape of amorphous sulfide solid electrolytes, but for example, particulate form can be used. The average particle size (D) of the particulate amorphous sulfide solid electrolyte. 50 Examples of these ranges include 0.01 μm to 500 μm and 0.1 μm to 200 μm.

[0056] (Crystalline sulfide solid electrolyte) The crystalline sulfide solid electrolyte obtained by the above method may be a so-called glass ceramic obtained by heating an amorphous sulfide solid electrolyte above its crystallization temperature, and its crystal structure may be Li3PS4, Li4P2S6, Li7PS6, or Li7P3S 11 Examples include crystal structures, and crystal structures having peaks near 2θ = 20.2° and 23.6° (for example, Japanese Patent Publication No. 2013-16423).

[0057] Li 4-x Ge 1-x P xS4-type thio-LISICON Region II crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148(7)A742-746 (2001)), Li 4-x Ge 1-x P x Other examples include crystal structures similar to the S4-type thio-LISICON Region II (see Solid State Ionics, 177 (2006), 2721-2725). Among the above, the thio-LISICON Region II type crystal structure is preferred for crystalline sulfide solid electrolytes obtained by the above method because it provides higher ionic conductivity. Here, "thio-LISICON Region II type crystal structure" refers to Li 4-x Ge 1-x P x S4-type thio-LISICON Region II crystal structure, Li 4-x Ge 1-x P x This indicates that the crystal structure is one of the S4-type thio-LISICON Region II or similar crystal structures. As will be discussed later, the thio-LISICON Region II crystal structure and the similar crystal structures are very similar in structure. Therefore, it is technically reasonable to treat the "thio-LISICON Region II crystal structure" as encompassing both the thio-LISICON Region II crystal structure and the similar crystal structures.

[0058] Here, if the sulfide solid electrolyte obtained by the above method contains lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms, then "Li 4-x Ge 1-x P x In the "S4 system thio-LISICON Region II type", "Li 4-x Ge 1-x P xmay not be represented by the compositional formula of S4 above. However, when having the same diffraction peaks as the above-mentioned "thio-LISICON Region II type crystal structure" (including the above-mentioned "similar crystal structure"), it can be said that the sulfide solid electrolyte obtained by the above method has a thio-LISICON Region II type crystal structure formed of lithium atoms, phosphorus atoms and sulfur atoms, preferably halogen atoms. This also applies to the argyrodite type crystal structure described later.

[0059] In X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, around 2θ = 17.5°, 18.3°, 26.1°, 27.3°, and 30.0°, the diffraction peaks of the Li4P2S6 crystal structure appear, for example, around 2θ = 16.9°, 27.1°, and 32.5°, the diffraction peaks of the Li7PS6 crystal structure appear, for example, around 2θ = 15.3°, 25.2°, 29.6°, and 31.0°, and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear, for example, around 2θ = 17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, and Li 4-x Ge 1-x P x The diffraction peaks of the S4-based thio-LISICON Region II type crystal structure appear, for example, around 2θ = 20.1°, 23.9°, and 29.5°, and Li 4-x Ge 1-x P x The diffraction peaks of the crystal structure similar to the S4-based thio-LISICON Region II type appear, for example, around 2θ = 20.2° and 23.6°. These peak positions may fluctuate within a range of ±0.5°.

[0060] A crystalline oxysulfide solid electrolyte having the structural skeleton of the above-mentioned Li7PS6 and having an argyrodite type crystal structure in which part of P is substituted with Si is also preferably mentioned. Examples of the compositional formula of the argyrodite type crystal structure include the compositional formula Li 7-x P 1-y Si yS6 and Li 7+x P 1-y Si y S6 (x is -0.6 to 0.6, y is 0.1 to 0.6) can be cited. The argyrodite-type crystal structure represented by this compositional formula is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks that mainly appear at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0061] As the compositional formula of the argyrodite-type crystal structure, the compositional formula Li 7-x-2y PS 6-x-y Cl x (0.8≦x≦1.7, 0<y≦-0.25x+0.5) can also be cited. The argyrodite-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks that mainly appear at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. Further, as the compositional formula of the argyrodite-type crystal structure, the compositional formula Li 7-x PS 6-x Ha x (Ha is Cl or Br, x is preferably 0.2 to 1.8) can also be cited. The argyrodite-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα rays, it has peaks that mainly appear at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. Note that these peak positions may fluctuate within a range of ±0.5°.

[0062] The crystalline sulfide solid electrolyte obtained by the above method preferably has at least one of the thiolysicon region II type crystal structure and the argyrodite type crystal structure. From the viewpoint of obtaining higher ionic conductivity, it is preferable that these crystal structures be included as the main crystal. In this specification, "included as the main crystal" means that the proportion of the target crystal structure among the crystal structures is 80% or more, preferably 90% or more, and more preferably 95% or more. Furthermore, from the viewpoint of obtaining higher ionic conductivity, it is preferable that the crystalline sulfide solid electrolyte obtained by the above method does not contain crystalline Li3PS4 (β-Li3PS4).

[0063] The composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms in a crystalline sulfide solid electrolyte is the same as the composition ratio (molar ratio) of lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms in the amorphous sulfide solid electrolyte described above.

[0064] There are no particular restrictions on the shape of the crystalline sulfide solid electrolyte, but for example, particulate form can be used. The average particle size (D) of the particulate crystalline sulfide solid electrolyte. 50 Examples of these ranges include 0.01 μm to 500 μm and 0.1 μm to 200 μm.

[0065] (Compounds containing carbon and oxygen atoms (coating material)) The compounds containing carbon atoms and oxygen atoms that can be used in this embodiment function as coating materials that cover the surface of sulfide solid electrolytes, providing excellent heat resistance and oxidation resistance. The above coating material is not particularly limited as long as it can coat the surface of the sulfide solid electrolyte, and examples include 1,2-butylene oxide, 1,2-epoxyoctane, 1,2-epoxyoctadecane, 2,2,3,3,4,4,5,5,5-nonafluoropentyloxirane, butylglycidyl ether, 2-ethylhexylglycidyl ether, 4-tert-butylphenylglycidyl ether, (S)-glycidyltrityl ether, tert-butyldimethylsilyl(S)-glycidyl ether, 1,1,1,3,5,5,5-heptamethyl-3-(3- Glycidyloxypropyl)trisiloxane, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, diethylene glycol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, diglycidyl resorcinol ether, 1,4-diglycidyloxybenzene, bisphenol A diglycidyl ether, 9,9-bis(4-glycidyloxyphenyl)fluorene, bisphenol A pro Poxylate diglycidyl ether, 1,3-bis(3-glycidyloxypropyl)tetramethyldisiloxane, trimethylolpropane triglycidyl ether, tris(4-hydroxyphenyl)methane triglycidyl ether, 2,4,6,8-tetramethyl-2,4,6,8-tetrakis(propylglycidyl ether)cyclotetrasiloxane, 1,3-butadiene diepoxide, 1,5-hexadiene diepoxide, 1,7-octadiene diepoxide, 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-di Compounds having a group selected from epoxy groups, glycidyl groups and glycidyl ether groups such as PSS-octa[(3-glycidyloxypropyl)dimethylsiloxy] substitution, as well as tert-butyldimethylsilyl(S)-glycidyl ether, 1,1,1,3,5,5,Compounds having epoxy groups such as 5-heptamethyl-3-(3-glycidyloxypropyl)trisiloxane and other compounds having epoxy and silyl groups; organic halides such as butyl iodide, octyl iodide, dodecyl iodide, benzyl bromide, 4-(trifluoromethyl)benzyl bromide, pentafluorobenzyl bromide, hexanoyl chloride, decanoyl chloride, 3,3-dimethylbutyryl chloride, octyl chloroformate, trimethylsilyl chloride; 1,3- Compounds comprising two or more heterocyclic rings having carbon and oxygen atoms, such as bis[2-(7-oxabicyclo[4.1.0]heptan-3-yl)ethyl]-1,1,3,3-tetramethyldisiloxane and 1,4-bis(2-tetrahydroflyroxy)butane (heteropolycyclic compounds); compounds having a formyl group (CH(=O)-), such as hexanal, heptanal, undecanal, benzyloxyacetaldehyde, and 2-[(tert-butyldimethylsilyl)oxy]acetaldehyde. Compounds having one or more acetyl groups (CH3C(=O)-), such as acetylacetone and benzyloxyacetone; compounds having two or more halogen-containing groups represented by -CH2X (where X represents a fluorine atom or a bromine atom) and organic groups, such as 1,3-dibromopropane, 1,4-dibromobutane, 1,6-dibromohexane, and 1,10-dibromodecane; thiol compounds such as 1-dodecanethiol, 1,10-decanedithiol, and 3-mercaptopropyltrimethoxysilane; Examples include metal-free phosphorus compounds such as ri-n-octylphosphine oxide, tri-n-octylphosphine, triphenylphosphine, 1,4-bis(diphenylphosphine)butane, bis[(2-diphenylphosphine)phenyl] ether, and 4,5-bis(diphenylphosphine)-9,9-dimethylxanthene (however, these compounds do not contain oxygen atoms that form a single bond with the phosphorus atom); and metal-free boron compounds such as tri-n-octyl borate and tri-n-octadecyl borate. The above-mentioned covering materials can be used individually or in combination of several types.

[0066] From the viewpoint of improving the oxidation resistance of the resulting modified sulfide solid electrolyte, the above coating material is preferably a compound having an epoxy group, an organic halide, or a compound having a formyl group, with a compound having an epoxy group being more preferred, and among these, 4-tert-butylphenyl glycidyl ether, 2-ethylhexyl glycidyl ether, and 1,1,1,3,5,5,5-heptamethyl-3-(3-glycidyloxypropyl)trisiloxane are even more preferred.

[0067] The content of the compound containing carbon and oxygen atoms (coating material) is preferably 0.03 parts by mass or more and 25.5 parts by mass or less per 100 parts by mass of sulfide solid electrolyte, more preferably 0.1 parts by mass or more and 20.0 parts by mass or less, even more preferably 0.5 parts by mass or more and 15.0 parts by mass or less, even more preferably 1.0 parts by mass or more and 10.0 parts by mass or less, and particularly preferably 1.5 parts by mass or more and 8.0 parts by mass or less. When the content of the coating material is within the above range, it is possible to more efficiently coat the surface of the sulfide solid electrolyte with the compound more uniformly. As a result, it is possible to more efficiently suppress the decrease in ionic conductivity and obtain excellent oxidation resistance.

[0068] As described above, the compound containing carbon atoms and oxygen atoms (coating material) is preferably attached to the surface of the sulfide solid electrolyte. In this case, the film thickness of the compound containing carbon atoms and oxygen atoms (coating material) is preferably 0.1 nm to 10 nm, more preferably 0.5 nm to 10 nm, and even more preferably 1.0 nm to 5.0 nm. With the above film thickness, it is easier to suppress the decrease in ionic conductivity and to obtain excellent oxidation resistance. Here, the film thickness of a compound (coating material) containing carbon atoms and oxygen atoms can be measured as follows. Ar +The results were derived from depth-direction XPS analysis using monomer ion sputtering. More specifically, O1s spectra were acquired every 30 seconds under predetermined sputtering conditions (1kV, 7mA, 2mm×2mm, sputtering rate of 1.6nm / min (in SiO2 equivalent)). Analysis was performed using MultiPak software from ULVAC-PHI. PS4 in spectra originating from S2p orbitals 3- Charge correction was performed using a peak position of 161.7 eV as the origin. The Shirley method was used for background subtraction. For each time i obtained, the O1s spectrum was separated into three waveform components, and the area ratio of each component [%] Sa i Sb i and Sc i (Sa i +Sb i +Sc i = 100. ) was calculated. i Sb i and Sc i The binding energies for each area value were set to 533.0–533.5 eV, 531.75–532.5 eV, and 530.75–531.5 eV, and the full width at half maximum was set to 1.2 or more and less than 1.6 eV. i Sa after the time when there was no change i Let S0 be the average value of S(CO) i =Sa i -S0 was defined as S(CO). i This is thought to be CO originating from the coating material. Normalize S(CO)0 to 1 when the sputtering time is 0 minutes, and then calculate T(CO) for each time. i =S(CO) i / S(CO)0 was calculated. Considering the effect of particle surface irregularities, T(CO) i The time when the value fell below 0.2 was considered the time when the coating material was no longer detectable, i.e., the particle surface from which the coating material had peeled off. The SiO2 equivalent film thickness corresponding to that time was calculated and this was taken as the film thickness.

[0069] The coverage rate of the compound (coating material) containing carbon atoms and oxygen atoms is preferably 60% or more, more preferably 75% or more, even more preferably 85% or more, and even more preferably 100%, based on the surface area of ​​the sulfide solid electrolyte, i.e., it is preferable that the entire surface is covered. The thickness of the coating material can be measured by cross-sectional observation using a transmission electron microscope (TEM), and the coverage rate can be calculated from the thickness of the coating material, elemental analysis values, and BET specific surface area.

[0070] (Manufacturing of modified sulfide solid electrolytes) The modified sulfide solid electrolyte of this embodiment has, for example, a BET specific surface area of ​​15 m². 2 / g or more 35m 2 It can be produced by a manufacturing method comprising mixing a sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms (which is less than or equal to / g), a compound containing carbon atoms and oxygen atoms (coating material), and an organic solvent, and then removing the organic solvent. As the sulfide solid electrolyte, the same sulfide solid electrolyte described as usable in the modified sulfide solid electrolyte of this embodiment is used. Therefore, as the sulfide solid electrolyte, a commercially available product may be used, or one manufactured by the above-mentioned method for producing sulfide solid electrolytes may be used. Furthermore, the compound containing carbon and oxygen atoms (coating material) can be the same as the coating material described as usable in the modified sulfide solid electrolyte of this embodiment.

[0071] Examples of organic solvents include those described as being usable in the method for producing the sulfide solid electrolyte described above. From the viewpoint of promoting the mixing of the sulfide solid electrolyte and the coating material, efficiently obtaining a modified sulfide solid electrolyte containing the sulfide solid electrolyte and the coating material, and further promoting the adhesion of the coating material to the sulfide solid electrolyte, among the above solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, and the ether solvents, ester solvents, and nitrile solvents exemplified as complexing agents are preferred. Among these, aromatic hydrocarbon solvents are more preferred. The above organic solvents can be used individually or in combination of several types.

[0072] The method for mixing the sulfide solid electrolyte, the coating material, and the organic solvent can be carried out by the same method as the "mixing" in the method for producing the sulfide solid electrolyte described above.

[0073] The removal of the organic solvent can be carried out by the same method as "drying" in the above-mentioned method for producing sulfide solid electrolytes. Furthermore, the "heating" step in the method for producing the sulfide solid electrolyte described above may also be performed.

[0074] (Properties of modified sulfide solid electrolytes) The modified sulfide solid electrolyte of this embodiment has a BET specific surface area of ​​15 m². 2 / g or more 35m 2 It is less than / g, and from the viewpoint of having better oxidation resistance, preferably 18m 2 / g or more 32m 2 / g or less, more preferably 20m 2 / g or more 30m 2 It is less than / g. Even if the surface of the modified sulfide solid electrolyte is covered with a coating material, it does not significantly affect the BET specific surface area of ​​the sulfide solid electrolyte, and the BET specific surface area of ​​the sulfide solid electrolyte used in this embodiment and the BET specific surface area of ​​the modified sulfide solid electrolyte are substantially the same. Therefore, the BET of the BET specific surface area of ​​the sulfide solid electrolyte is 15 m². 2 / g or more 35m 2 If a substance of less than / g is used, the BET specific surface area of ​​the modified sulfide solid electrolyte will naturally be 15m². 2 / g or more 35m 2 This will be less than / g.

[0075] The oxidation current of the modified sulfide solid electrolyte in this embodiment is preferably reduced by 3.0% or more, more preferably by 5.0% or more, even more preferably by 7.5% or more, even more preferably by 10.0% or more, and particularly preferably by 12.5% ​​or more. Here, the reduction rate of the oxidation current is calculated by the following formula. The modified sulfide solid electrolyte of this embodiment comprises a sulfide solid electrolyte having a specific specific surface area and a compound (coating material) containing carbon and oxygen atoms, and has a specific ratio of the O1s spectrum to the area of ​​specific S2p and P2p spectra, thereby preferably keeping the rate of decrease in oxidation current within the above range. As a result, the modified sulfide solid electrolyte of this embodiment has superior oxidation resistance.

[0076] The percentage decrease in oxidation current (%) = (oxidation current 2 - oxidation current 1) / oxidation current 2 × 100 Oxidation current 1: Oxidation current (μA) of the modified sulfide solid electrolyte. Oxidation current 2: Oxidation current (μA) of the sulfide solid electrolyte before modification.

[0077] Furthermore, the oxidation current of the modified sulfide solid electrolyte in this embodiment cannot be stated definitively as an absolute value because it can vary depending on the measurement conditions, etc. However, when measured using the oxidation current measurement method described later in the examples, it is preferably 0.57 μA or less, more preferably 0.56 μA or less, even more preferably 0.55 μA or less, even more preferably 0.52 μA or less, and particularly preferably 0.50 μA or less.

[0078] The modified sulfide solid electrolyte of this embodiment is solid 1 H- 6 In Li CP / MAS NMR measurements, it is preferable that the chemical shift observed has a broad peak at 0.5 to 1.2 ppm and a sharp peak at -0.2 to 0.5 ppm within a chemical shift of -0.2 to 1.2 ppm. In this specification, a "broad peak" means a peak that is broad relative to a "sharp peak" as described above, and means a peak with a full width at half maximum of 50 Hz or more. In this specification, solid 1 H- 6 Li CP / MAS NMR measurements are performed according to the methods described in the examples, and the areas of broad and sharp peaks are also determined according to the methods described in the examples.

[0079] A broad peak is preferably observed at a chemical shift of 0.5 to 1.2 ppm, and a sharp peak is preferably observed at a chemical shift of -0.2 to 0.5 ppm. Furthermore, the area of ​​the broad peak at a chemical shift of 0.5 to 1.2 ppm (A) B ) and the area of ​​the sharp peak at chemical shift -0.2 to 0.5 ppm (A S The area of ​​the broad peak (A) relative to the total area of ​​) B The ratio of (hereinafter also referred to as the "broad peak ratio") is preferably 10.0% or more and 65.0% or less. When the broad peak ratio is within the above range, it will have better oxidation resistance. From the same viewpoint, the broad peak ratio is preferably 12.5% ​​or more, more preferably 15.0% or more, even more preferably 20.0% or more, and as an upper limit, preferably 62.5% or less, more preferably 60.0% or less, and even more preferably 57.5% or less.

[0080] The ionic conductivity of the modified sulfide solid electrolyte in this embodiment cannot be generalized as it varies depending on its crystal structure, but it is usually 0.5 mS / cm or higher, and more specifically 1.0 mS / cm or higher, 1.2 mS / cm or higher, and 1.5 mS / cm or higher. Although the ionic conductivity of the modified sulfide solid electrolyte in this embodiment is lower than that of the sulfide solid electrolyte before modification, it still maintains a high ionic conductivity as described above, and it can be said that the decrease in ionic conductivity is sufficiently suppressed.

[0081] (Application) The modified sulfide solid electrolyte of this embodiment has excellent oxidation resistance and high ionic conductivity, and therefore exhibits excellent battery performance, making it suitable for use in batteries. The modified sulfide solid electrolyte of this embodiment may be used in the positive electrode layer, the negative electrode layer, or the electrolyte layer. Each layer can be manufactured by known methods.

[0082] (electrode composite material) When the modified sulfide solid electrolyte of this embodiment is used as an electrode mixture, it can be used as an electrode mixture containing the modified sulfide solid electrolyte and an electrode active material. As electrode active materials, positive electrode active materials and negative electrode active materials are selected depending on whether the electrode composite material is used as the positive electrode or the negative electrode. Conventional materials that have been used as such for the positive and negative electrode active materials can be used. In addition to the modified sulfide solid electrolyte and electrode active material, the product may also contain other components such as conductive materials and binders.

[0083] (Lithium-ion battery) When the modified sulfide solid electrolyte of this embodiment is used as a battery, it can be used as a lithium-ion battery containing at least one of the above-mentioned modified sulfide solid electrolyte and the above-mentioned electrode composite material. Furthermore, the above-mentioned battery preferably uses a current collector in addition to the positive electrode layer, electrolyte layer, and negative electrode layer, and known current collectors can be used. For example, a layer coated with gold or the like, which reacts with the above-mentioned solid electrolyte, such as Au, Pt, Al, Ti, or Cu, can be used. [Examples]

[0084] The present invention will now be specifically described with reference to examples, but the present invention is not limited in any way by these examples.

[0085] (Manufacturing Example 1: Preparation of sulfide solid electrolyte) In a Schlenk flask (capacity: 100 mL) containing a stirring bar, 0.59 g of lithium sulfide, 0.95 g of phosphorus pentasulfide, 0.19 g of lithium bromide, and 0.28 g of lithium iodide were introduced under a nitrogen atmosphere. After rotating the stirring bar, 20 mL of the complexing agent tetramethylethylenediamine (TMEDA) was added, and stirring was continued for 12 hours. The resulting complex-containing material was dried under vacuum (room temperature: 23°C) to obtain a complex powder. Next, the complex powder was heated under vacuum at 120°C for 2 hours to obtain an amorphous sulfide solid electrolyte. Furthermore, the amorphous sulfide solid electrolyte was heated under vacuum at 140°C for 1.5 hours while shaking well to obtain a crystalline sulfide solid electrolyte (the heating temperature for obtaining the crystalline sulfide solid electrolyte (140°C in this example) is sometimes referred to as the "crystallization temperature"). The BET specific surface area of ​​the obtained amorphous sulfide solid electrolyte and crystalline sulfide solid electrolyte was measured, and both were found to be 25 m². 2 It was / g.

[0086] (Example 1) In a Schlenk flask (capacity: 100 mL) with a stirring bar, 3 g of the crystalline sulfide solid electrolyte obtained in Production Example 1 was weighed and added under a nitrogen atmosphere. 22 g of toluene was added and the mixture was stirred to form a slurry. To this slurry, 0.075 g of 4-tert-butylphenyl glycidyl ether (2.5% by mass relative to 100% by mass of the crystalline sulfide solid electrolyte) was added as a coating material. After stirring for 24 hours, the toluene was removed by vacuum drying to obtain a modified sulfide solid electrolyte. The obtained modified sulfide solid electrolyte was measured by X-ray photoelectron spectroscopy (XPS) and the composition ratio of the P2p spectrum obtained from the results of the measurement was determined according to the following method (A P2p ) and composition ratio of the S2p spectrum (A S2p The area ratio of CO from the coating material in the O1s spectrum to the total of (B C-O ) ratio (B C-O / ( A P2p +A S2pThe following measurements were performed: calculation of )), CV measurement (oxidation current), calculation of the rate of decrease in oxidation current based on said measurement, measurement of the area of ​​broad peaks, the area of ​​sharp peaks, the ratio of the area of ​​broad peaks, and the ionic conductivity. The measurement results and calculation results are shown in Table 1.

[0087] (Examples 2-6 and Comparative Example 1) In Example 1, a modified sulfide solid electrolyte was prepared in the same manner as in Example 1, except that the amount of coating material used was as shown in Table 1. Furthermore, the sulfide solid electrolyte obtained in Production Example 1 was used as the sulfide solid electrolyte for Comparative Example 1. The modified sulfide solid electrolytes obtained in Examples 2-6 and the sulfide solid electrolyte of Comparative Example 1 were measured by X-ray photoelectron spectroscopy (XPS) and the composition ratio of the P2p spectra obtained from the results of the measurement was determined according to the following method (A P2p ) and S2p composition ratio (A S2p The area ratio of CO from the coating material in the O1s spectrum to the total of (B C-O ) ratio (B C-O / ( A P2p +A S2p The following were performed: calculation of )), CV measurement (oxidation current), calculation of the rate of decrease in oxidation current due to said measurement, and measurement of ionic conductivity. The measurement results and calculation results are shown in Table 1. In addition, for Examples 4 and 6, the area of ​​broad peaks, the area of ​​sharp peaks, and the ratio of the area of ​​broad peaks are also shown in Table 1.

[0088] (1) Measurement by X-ray photoelectron spectroscopy (XPS) XPS measurements were performed on the modified sulfide solid electrolytes obtained in Examples 1-6 and the sulfide solid electrolyte of Comparative Example 1. In a glove box controlled to an Ar atmosphere with a dew point of -60°C or lower, double-sided tape (made of carbon) was attached to a metal substrate, and the powder sample was pressed onto the tape with a spatula (approximately 5 mm in diameter). The spatula used had its surface cleaned with an organic solvent such as acetone. To prevent the sample from being exposed to the atmosphere, it was introduced into the XPS apparatus using a transfer vessel, and the measurement was performed. The apparatus and detailed measurement conditions used for the XPS measurement are shown below.

[0089] XPS system: VersaProbeII (product name), manufactured by ULVAC-PHI Corporation. X-ray source: Monochromatic AlKα rays (1486.6 eV) were used, and measurements were taken under high-power conditions of 100 W. X-ray diameter: 100 μm (measured by sweeping within a range of 200 μm × 1200 μm) Passage energy: 23.5 eV (C1s, O1s, S2p, P2p) 46.95 eV (Li1s,Br3d,I3d5 / 2) Step energy: 0.1 eV (C1s, O1s, S2p, P2p) 0.2eV (Li1s,Br3d,I3d5 / 2) Photoelectron detection angle: 45°

[0090] The analysis software used was "MultiPak" (product name) (manufactured by ULVAC-PHI, Inc.). Background was subtracted from each spectrum using the Shirley method, and the composition ratio was calculated using the relative sensitivity coefficient from the resulting area intensity. Of the calculated composition ratios, the composition ratio of the P2p spectrum was selected as A. P2p The composition ratio of the S2p spectrum is A S2p That's what I decided.

[0091] The Sa i For this purpose, determine the Sa0 value for modified sulfide solid electrolyte and sulfide solid electrolyte (uncoated) at a sputtering time of 0 minutes, and subtract the Sa0 value of the sulfide solid electrolyte (uncoated) from the value of B. C-O This was defined as B. C-O This is thought to be the area ratio of CO originating from the coating material in the O1s spectrum of the outermost surface. P2p , A S2p , Sa0 and B C-O The value was calculated as the average of three arbitrary points within the measurement area (5 mm in diameter).

[0092] Figure 1 shows the spectra obtained by X-ray photoelectron spectroscopy (XPS) for the modified sulfide solid electrolytes of Examples 1, 4, and 6 and the sulfide solid electrolyte of Comparative Example 1.

[0093] (2) CV measurement (measurement of oxidation current) The following CV measurement cell was used for CV measurement (measurement of oxidation current). 100 mg of solid electrolyte for the separator layer was added to a 10 mm diameter measuring cell and pressed three times at 400 MPa using a uniaxial press. Between each press, the cell was rotated 120°, and the third press was held for 5 minutes. Next, 100 mg of the solid electrolyte obtained in the example or comparative example was added and pressed three times in the same manner. Furthermore, the cell was inverted and pressed at 400 MPa for 5 minutes. Carbon-coated aluminum foil was placed on top of the solid electrolyte of the example or comparative example as a current collector foil. Li / Cu foil (φ10 mm, 0.03 / 0.01 mmt) was placed on the opposite side of the solid electrolyte for the separator layer from the solid electrolyte of the example or comparative example, and pressed at 40 MPa for 5 minutes. The cell was fastened with M8 bolts at 8 N·m to complete the measuring cell.

[0094] The electrolyte for the separator described above was synthesized under the following conditions. In a 1L reaction vessel equipped with a stirring blade, 20.5g of Li2S, 33.1g of P2S5, 10.0g of LiI, and 6.5g of LiBr were added under a nitrogen atmosphere. After rotating the stirring blade, 630g of toluene was introduced, and the slurry was stirred for 10 minutes. The reaction vessel was connected to a bead mill capable of circulating operation ("Star Mill LMZ015 (product name)", manufactured by Ashizawa Fine Tech Co., Ltd., zirconia bead material: zirconia, bead diameter: 0.5mmφ, bead usage: 456g), and a grinding process was performed for 45 hours (pump flow rate: 650mL / min, bead mill peripheral speed: 12m / min, mill jacket temperature: 45℃). The obtained slurry was dried at room temperature under vacuum (25°C) and then heated (80°C) to obtain an amorphous white powder of sulfide solid electrolyte. Furthermore, the obtained white powder was heated at 195°C for 2 hours under vacuum to obtain a crystalline white powder of sulfide solid electrolyte. In the XRD spectrum of the crystalline sulfide solid electrolyte, crystallization peaks were detected at 2θ = 20.2° and 23.6°, confirming that it has a thiolysicon region type II crystal structure. In addition, the average particle size (D) of the obtained crystalline sulfide solid electrolyte was determined. 50 The sieve diameter was 4.5 μm, and the ionic conductivity was 5.0 mS / cm.

[0095] An InLi foil (with a layered structure, where " / " indicates the space between layers; In: 10mmφ × 0.1mm / Li: 9mmφ × 0.08mm / SUS: 10mmφ × 0.1mm) is placed on the opposite side of the electrolyte measurement powder A for the separator layer, and the pressure is 6 MPa / cm². 2 It was pressed once. The cell was fixed with four screws with an insulator in between to prevent a short circuit between the measurement powder (1) and the InLi foil, and the screws were tightened with a torque of 8 N·m to obtain the measurement cell.

[0096] The obtained measurement cell was connected to a measuring instrument ("VSP-3 (model number)", manufactured by Biologic), and a CV curve was obtained under the following conditions. The maximum current in the CV curve was defined as the oxidation current. Measurement temperature: 25℃ Sweep speed: 0.1mV / s Potential measurement range: Open circuit voltage (+2.7V) → +5.0V → +2.7V Number of cycles: 5

[0097] Figure 2 shows the CV curves at the 5th cycle of the above CV measurement for the modified sulfide solid electrolytes of Examples 1 to 6 and the sulfide solid electrolyte of Comparative Example 1.

[0098] (3) Decrease rate of oxidation current Based on the above (CV measurement (oxidation current)), the oxidation current 2 of the sulfide solid electrolyte obtained in Production Example 1 (i.e., the sulfide solid electrolyte of Comparative Example 1) and the oxidation current 1 of the modified sulfide solid electrolyte obtained in Examples 1 to 6 and the sulfide solid electrolyte of Comparative Example 1 were used to calculate the oxidation current reduction rate using the following formula. The percentage decrease in oxidation current (%) = (oxidation current 2 - oxidation current 1) / oxidation current 2 × 100 Oxidation current 1: Oxidation current (μA) of the modified sulfide solid electrolyte. Oxidation current 2: Oxidation current (μA) of the sulfide solid electrolyte before modification.

[0099] (4) Ionic conductivity Using the modified sulfide solid electrolytes obtained in Examples 1-6 and the sulfide solid electrolyte of Comparative Example 1, a diameter of 10 mm (cross-sectional area S: 0.785 cm²) was prepared. 2 ), circular pellets with a height (L) of 0.1 to 0.3 cm were formed as samples. Electrode terminals were taken from the top and bottom of the samples, and measurements were taken at 25°C using the AC impedance method (frequency range: 1 MHz to 100 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency region, the real part Z'(Ω) at the point where -Z''(Ω) is minimized was taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(mS / cm) was calculated according to the following formula. R = ρ(L / S) σ = 1 / ρ

[0100] (5)Solid 1 H- 6 Li CP / MAS NMR measurement Regarding the modified sulfide solid electrolytes obtained in Examples 1, 4, and 6 and the sulfide solid electrolyte of Comparative Example 1, 1 H- 6 Measurements were performed using Li CP / MAS NMR. Solid state 1 H- 6 The Li CP / MAS NMR measurements were performed using the following instrument and under the following conditions. The measurement results were analyzed using the following method, and the area of ​​the broad peak (A) was determined. B ) and the area of ​​the sharp peak (AS ) is determined, and the area of ​​the broad peak (A) is determined relative to the total area of ​​these. B The ratio of ) was calculated.

[0101] NMR spectrometer: ECZL400G (product name), manufactured by JEOL Ltd. Magnetic field strength: 400MHz Detector: 3.2mm Auto MAS probe Solid NMR sample tube diameter: 3.2mm Observed nuclei: 6 Li Observation frequency: 58.832MHz Measurement temperature: room temperature Pulse sequence: CP / MAS method Conditions for cross-polarization: 90° pulse width ( 1 H): 3.06 μs Observed nucleus CP pulse shape: RAMP CP Spinlock strength: 32.8kHz ( 6 Li), 40.9kHz( 1 H) Contact time: 10ms During CP 1 The spinlock strength of H is kept constant (40.9 kHz). 6 The spinlock strength of Li was linearly varied from 33.8 kHz to 31.8 kHz. Decoupling conditions ( 1 H): Decoupling pulse series: TPPM Decoupling power: 81.8kHz Decoupling phase: 15° Pulse irradiation center: 5 ppm Waiting time after FID measurement until the next pulse is applied: 6 seconds Number of points when FID was acquired: 4,096 MAS (Magic Angle Rotation) rotation speed: 10kHz Total number of times: 5,000 Measurement range: 250 ppm to -250 ppm External standard: Lithium iodide (chemical shift -4.74 ppm)

[0102] (Data processing conditions) An exponential function was used as the window function, and a line broadening value of 5 Hz was used. Zero filling was performed once.

[0103] (Peak separation) The peak separation is obtained from the solid 1 H- 6 The analysis was performed by examining the Li CP / MAS NMR spectrum. More specifically, the solid 1 H- 6 For each NMR peak (experimental value) on the Li CP / MAS NMR spectrum, a nonlinear least squares method was used, and for the calculation of peak separation, the Lorentz function or pseudo-Voigt function was used within the chemical shift range of peaks 1 to 3 (as shown in Table A below). Calculated values ​​of NMR peaks and sum of squared residuals R 2 Calculate the value and find the smallest sum of squared residuals R 2 The peak separation results that provided values ​​were adopted. The assignment of each peak was determined according to Table A below.

[0104] [Table 1]

[0105] Measurement of the modified sulfide solid electrolytes obtained in Examples 1, 4, and 6 revealed that peaks 1 and 2 were sharp peaks, while peak 3 was a broad peak. The areas of peaks 1 to 3, determined by the above (peak separation) method, were designated A1 to A3, respectively, and the ratio of the broad peak areas was calculated using the following formula. Table 1 shows the area of ​​each peak and the broad peak ratio for the modified sulfide solid electrolytes of Examples 1, 4, and 6, and the sulfide solid electrolyte of Comparative Example 1. Area of ​​sharp peaks (A S ) = Area of ​​Peak 1 (A1) + Area of ​​Peak 2 (A2) Area of ​​broad peak (A B ) = Area of ​​Peak 3 (A3) Area of ​​broad peak (A B ) ratio = area of ​​broad peak (A B) / (Area of ​​sharp peaks (A S ) + area of ​​broad peak (A B )) × 100

[0106] Furthermore, the NMR spectra obtained by NMR measurements of the modified sulfide solid electrolytes of Examples 1, 4, and 6, and the sulfide solid electrolyte of Comparative Example 1, are shown in Figures 3 to 6, respectively.

[0107] [Table 2]

[0108] BET specific surface area is 15m 2 / g or more 35m 2 The modified sulfide solid electrolytes of Examples 1 to 8, which include a sulfide solid electrolyte with a concentration of 0.5 / g or less and a coating material, all have a composition ratio (A) of the P2p spectrum of the outermost surface, measured by X-ray photoelectron spectroscopy (XPS). P2p ) and composition ratio of the S2p spectrum (A S2p The area ratio of CO from the coating material in the O1s spectrum to the total of (B C-O ) ratio (B C-O / ( A P2p +A S2p The oxidative current (I / O) was between 0.010 and 0.075, and the decrease in oxidation current was significant at over 15.5%, confirming excellent oxidation resistance. Furthermore, the ionic conductivity was also high at 1.2 to 2.1 (mS / cm), and the decrease in ionic conductivity was suppressed, confirming that it can exhibit excellent battery performance. [Industrial applicability]

[0109] The modified sulfide solid electrolyte of this embodiment has excellent oxidation resistance and high ionic conductivity, and therefore possesses excellent battery performance. For this reason, it is particularly suitable for use in lithium-ion batteries, especially those used in automotive applications, as well as in information-related equipment and communication devices such as personal computers, video cameras, and mobile phones, and especially in all-solid-state batteries.

Claims

1. BET specific surface area is 15 m² 2 / g or more 35m 2 A sulfide solid electrolyte containing a concentration of 0.5 / g or less, and a compound containing carbon and oxygen atoms, is used, and the composition ratio of the P2p spectrum of the outermost surface, measured by X-ray photoelectron spectroscopy (XPS), is (A P2p ) and composition ratio of the S2p spectrum (A S2p The ratio of the area of ​​C-O from the compound in the O1s spectrum to the total of (B C-O ) ratio (B C-O / (A P2p +A S2p A modified sulfide solid electrolyte having a ratio of 0.010 to 0.

075.

2. The modified sulfide solid electrolyte according to claim 1, wherein the content of the compound containing carbon atoms and oxygen atoms is 0.03 parts by mass or more and 25 parts by mass or less per 100 parts by mass of the sulfide solid electrolyte.

3. The modified sulfide solid electrolyte according to claim 1 or 2, wherein the compound containing carbon atoms and oxygen atoms is a compound having an epoxy group.

4. solid 1 H- 6 In Li CP / MAS NMR measurement, the area of the broad peak at a chemical shift of 0.5 to 1.2 ppm observed (A B ), and the area of the sharp peak at a chemical shift of -0.2 to 0.5 ppm (A S ), relative to the total area of the above, the area of the peak at 0.5 to 1.2 ppm (A B ) is 10.0% or more and 65.0% or less, the modified sulfide solid electrolyte according to any one of claims 1 to 3.

5. The modified sulfide solid electrolyte according to any one of claims 1 to 4, wherein the rate of decrease of the oxidation current measured by cyclic voltammetry (CV measurement), calculated by the following formula, is 3.0% or more. The rate of decrease in oxidation current (%) = (oxidation current 2 - oxidation current 1) / oxidation current 2 × 100 Oxidation current 1: Oxidation current (mA) of the modified sulfide solid electrolyte. Oxidation current 2: Oxidation current (mA) of the sulfide solid electrolyte before modification.

6. The modified sulfide solid electrolyte according to any one of claims 1 to 5, wherein the sulfide solid electrolyte comprises lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms.

7. The modified sulfide solid electrolyte according to any one of claims 1 to 6, wherein the sulfide solid electrolyte includes at least one of the crystal structures of a thiolysicon region II type crystal structure and an argyrodite type crystal structure.

Citation Information

Patent Citations

  • Modified sulfide solid electrolyte and method for producing same

    WO2022158458A1